LEGAL REVIEW OF THE PROTECTION OF CONSUMER PERSONAL DATA IN E-COMMERCE TRANSACTIONS UNDER LAW NUMBER 27 OF 2022 - Muhammad Syafei; Rahmayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The enactment of Law No. 27 of 2022 on Personal Data Protection (PDP Law) marks a significant milestone in efforts to strengthen legal protections for consumers’ personal data in Indonesia. These regulations on personal data protection are expected to bring Indonesia on par with developed nations that have implemented personal data protection laws, such as the European Union with its General Data Protection Regulation (GDPR). This will further promote and strengthen Indonesia’s position as a trusted business hub, which is a key strategy in Indonesia’s national economy. The obligation to implement adequate security measures is a crucial aspect of e-commerce platforms’ responsibilities, encompassing the implementation of technical, organizational, and administrative security measures. Technically, e-commerce platforms are required to implement data encryption, multi-layered authentication systems, real-time security monitoring, regular data backups, and incident response mechanisms. Prior to the enactment of Law No. 27 of 2022 on Personal Data Protection (PDP Law), Indonesia faced a legal vacuum in regulating the specific responsibilities of digital platform operators regarding personal data security. Reliance on Law No. 11 of 2008 on Electronic Information and Transactions (EIT Law), which is of a general nature, has proven inadequate to address the complexities of data protection issues in the digital era.